Mechanical properties and antioxidant activity of carrageenan-cellulose nanofiber incorporated butylated hydroxyanisole as active food packaging - Wan Amnin, Wan Yahaya; Syed Mohd Saufi, Tuan Chik; Nurul Aini, Mohd Azman; Adibi, M. Nor; Khadijah Husna, Abd Hamid; Azilah, Ajit (Elsevier Ltd, 2024)
Incorporated Butylated Hydroxyanisole (BHA) in biopolymer film is one of strategy to minimize the direct contact of BHA into the food product without limits their function as food preservative. Thus, the aim of this study was to formulate the active packaging film using semi refined carrageenan (SRC) biopolymer plasticized with glycerol (G), reinforced with 10% v/v cellulose nanofiber (CNF) and incorporated antioxidant agent (BHA) with different concentrations (0.1 to 0.4% w/v) as antioxidants. Physical properties, including thickness, opacity, moisture content, and solubility in water, as well as mechanical properties such as tensile strength (TS) and elongation at break (EAB) were analyzed. Fourier transform infrared (FTIR) analysis, morphology, and contact angle measurements were also performed. The results showed that the incorporation of BHA reduced the tensile strength and elongation at break of the active SGC-BHA films. However, the film's solubility, opacity, thickness, and moisture content improved with an increase in BHA concentration. The contact angle results revealed interesting trends, indicating changes in the film's surface properties with increasing BHA concentration. These findings suggest that the new formulation of active films may offer a viable alternative for plastic food packaging. By avoiding direct contact with synthetic preservatives, the films have the potential to extend the shelf life of food products while still providing the benefits of an antioxidant agent.